THERMOCHEMICAL PROPERTIES OF INBRED AND HYBRID RICE BIOMASS FEEDSTOCK FOR BIOENERGY CONVERSION - Regalado, Manuel Jose C.; Belonio, Alexis T.; Villota, Katherine C.; Castillo, Phoebe R.; Gagelonia, Eden C. (International Journal For Research In Agricultural And Food Science, 2018)
The husks and straw produced from cultivating and processing of rice are the most commonly available biomass for conversion to bioenergy. Basic data on biomass properties are necessary for the analysis, design, and evaluation of any thermochemical conversion processes. The study provides information on heating value, proximate and ultimate compositions of these rice residues including rice husk char from popular Philippine inbred and hybrid cultivars, NSIC Rc222 and NSIC Rc132H, respectively. Results showed high volatile matter ranging from 57.7 to 65.5% and low ash content ranging from 17.4 to 25.1%, making these rice residues as ideal feedstock for gasification and pyrolysis. The ultimate analysis indicated carbon, oxygen and hydrogen as the major elemental constituents with weight fraction ranged from 21.64 to 40.83%, 2.0 to 36.3%, 0.43 to 4.99% respectively. The obtained low fraction of N and S which ranging from 0.23 to 0.68% and 0.02 to 0.1%, respectively, indicate that these rice residues are environment friendly fuel. The high and low heating values varied from 7.02 to 15.89MJ/kg.